Building TEPANG, Startup team and Digital Platform, by using Agile-Simplified-Lean- Design-Thinking Approach - Ignatius Wiseto Prasetyo Agung; Iedam Fardian Anshori; Panji Firman; Zulhamdi Koto; Ajeng Novia Berliani; Fitra Agustina Sa'adah (Proceeding International Conference on Information Technology and Business, 2022)
Currently, futsal, mini soccer and football are becoming more popular in Indonesia. Many field owners rent out their fields to players at a fairly affordable price. Besides, there are several football courses in various cities. However, there are still many problems for players and field managers, as well as for football course/school/academy managers. For players who want to rent the field, they need to access the information of the location, facilities, available time slots and their rates. For the field owners, sometimes they have problems with the unrecorded payment in cash. For football school managers, the system for managing the instructors, students and course publicity is also needed. This paper shows the process of building a solution to address those problems in three phases namely customer discovery, agile product development, and operational preparation strengthening startup solidity. The authors propose this Agile-Simplified-Lean-Design-Thinking approach for solving customers' problems, developing the web apps, as well as mapping the business model. During this process, three customer segment representatives were involved to validate the problem's solution. This developed platform and startup team, called TEPANG - Ketemu di Lapang, are important as the bases for its future company building. Keywords— startup, lean, design, thinking, agile